2018
DOI: 10.1128/mbio.01393-18
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase and Guanylate Binding Protein 5 Restrict Survival of Avirulent Type III Strains of Toxoplasma gondii in Naive Macrophages

Abstract: Toxoplasma infections in humans and other mammals are largely controlled by IFN-γ produced by the activated adaptive immune system. However, we still do not completely understand the role of cell-intrinsic functions in controlling Toxoplasma or other apicomplexan infections. The present work identifies intrinsic activities in naive macrophages in counteracting T. gondii infection. Using an avirulent strain of T. gondii, we highlight the importance of Nox complexes in conferring protection against parasite infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 76 publications
5
40
0
Order By: Relevance
“…Mice surviving to chronic infection were killed, and half of their brains was harvested in 1 mL of 6% (vol/vol) formaldehyde and 0.25% (vol/vol) Triton X-100 in cold PBS. Cyst burden in each sample was estimated as described previously (68). Cysts were stained with 20 μg/mL FITC-conjugated DBL in 10% goat serum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mice surviving to chronic infection were killed, and half of their brains was harvested in 1 mL of 6% (vol/vol) formaldehyde and 0.25% (vol/vol) Triton X-100 in cold PBS. Cyst burden in each sample was estimated as described previously (68). Cysts were stained with 20 μg/mL FITC-conjugated DBL in 10% goat serum.…”
mentioning
confidence: 99%
“…or 5 ME49 cysts orally. Mice were killed 3 and 6 d postinfection with PRU KO, followed by isolation of the peritoneal cells as described previously (68). In ME49 cyst infection, the mice were first perfused with PBS and half of the brain was removed and kept in RPMI.…”
mentioning
confidence: 99%
“…Like the IRGs, GBPs also accumulate on the PVM shortly after invasion by T. gondii, an action which is inhibited by virulent strains of the parasite. Unlike the IRGs, which cause direct disruption of the PVM, GBPs act by recruiting protein complexes to the membrane, such as the inflammosome, autophagy apparatus, and NOX2 NADPH oxidase, which have antimicrobial functions [35,36,37,38,39]. In the current study, the majority of known GBPs from both the chromosome 3 and 5 clusters were found to be upregulated during infection with all three strain types.…”
Section: Discussionmentioning
confidence: 48%
“…IFA was carried out as previously described [12]. Briefly, cells grown on coverslips in a 24-well plate were fixed with 4% paraformaldehyde in phosphate-buffered saline (PBS) for 10 min and permeabilized with 0.25% triton-PBS for 10 min.…”
Section: Ifamentioning
confidence: 99%
“…Interestingly, infections by both avirulent Type III (CTG strain) and virulent Type I (GT1 strain) trigger ROS production in the infected macrophages. CTG-strain parasites are mainly cleared by the naive macrophages in a manner depending on NADPH oxidase-generated ROS without activation of interferon gamma [12]. Due to ROS' potential detrimental impact on DNA, we explored the association between elevated ROS levels and host DNA damage during T. gondii infection.…”
Section: Introductionmentioning
confidence: 99%